Foreign demand shocks to production networks: Firm responses and worker impacts - Emmanuel Dhyne; Ayumu Ken Kikkawa; Toshiaki Komatsu; Magne Mogstad; Felix Tintelnot (National Bank of Belgium, 2022)
We quantify and explain the firm responses and worker impacts of foreign demand shocks to domestic production networks. To capture that firms can be indirectly exposed to such shocks by buying from or selling to domestic firms that import or export, we use Belgian data with information on both domestic firm-to-firm sales and foreign trade transactions. Our estimates of firm responses suggest that Belgian firms pass on a large share of a foreign demand shock to their domestic suppliers, face upward-sloping labor supply curves, and have sizable fixed overhead costs in labor. Motivated and guided by these findings, we develop and estimate an equilibrium model that allows us to study how idiosyncratic and aggregate changes in foreign demand propagate through a small open economy and affect firms and workers. Our results suggest that the way the labor market is typically modeled in existing research on foreign demand shocks - with no fixed costs and perfectly elastic labor supply - would grossly understate the decline in real wages due to an increase in foreign tariffs.
Keywords: F16; J22; E00; 330; Production networks; Foreign demand shocks; Imperfect labor market; Fixed costs; Nachfrage; Außenhandel; Schock; Wirkungsanalyse; Unternehmensnetzwerk; Beschäftigungseffekt; Belgien